2020
DOI: 10.1007/s11682-020-00294-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological effects of perceived stress are different between adolescents and middle-aged adults

Abstract: Stress is an inevitable element of everyday living. Developmental studies suggested that adolescents are more vulnerable and sensitive to the effect of stress due to their developing brains, especially in areas related to stress perception and processing. This voxel-based morphometry study examined the association between various neurobiological markers and the level of perceived stress experienced by adolescents (n = 26) and middle-aged adults (n = 26). Our findings indicated that differences existed in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Indeed, a clinical study revealed that right amygdala stimulation triggered negative emotions and left amygdala stimulation induced both pleasant and unpleasant emotions ( Lanteaume et al, 2007 ). Interestingly, and in contrast, the recent study of Wu et al has also shown a significant interaction effect of stress by age on a cluster extending to the left amygdala ( Wu et al, 2020 ); indeed, post-hoc comparisons revealed a positive association with left amygdala volumes in adolescents, with middle-aged adults presenting a negative correlation with PSS levels, which may justify the weaker effect observed on the left hemisphere.…”
Section: Discussionmentioning
confidence: 58%
“…Indeed, a clinical study revealed that right amygdala stimulation triggered negative emotions and left amygdala stimulation induced both pleasant and unpleasant emotions ( Lanteaume et al, 2007 ). Interestingly, and in contrast, the recent study of Wu et al has also shown a significant interaction effect of stress by age on a cluster extending to the left amygdala ( Wu et al, 2020 ); indeed, post-hoc comparisons revealed a positive association with left amygdala volumes in adolescents, with middle-aged adults presenting a negative correlation with PSS levels, which may justify the weaker effect observed on the left hemisphere.…”
Section: Discussionmentioning
confidence: 58%
“…Three studies involved middle-aged adults (ie, 36-55 years old) [ 82 , 102 , 113 ]. Based on emerging results, the use of COTS games can offer essential support for people of this age group, who, besides representing the most significant percentage of video game players [ 14 ], are particularly susceptible to high stress and anxiety [ 128 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed neither a significant correlation of COVID-19 proximity to IA nor any psychopathologies, both of which were significant within the Indonesian adult population. This could be assumed due to differences in stress perception (immediate vs. distant) ( 44 ) and emotional regulation ( 45 ) to differing psychological stressors during the COVID-19 pandemic, which could be scrutinized in the future. Notably, the average age of first Internet use among children in European countries was estimated around 8 years old ( 46 ); meanwhile, among American adolescents, the mean age of first Internet use was about 9 years old ( 47 ).…”
Section: Discussionmentioning
confidence: 99%